1979
DOI: 10.1002/ijc.2910240514
|View full text |Cite
|
Sign up to set email alerts
|

Rauscher leukemia virus‐induced tumor antigens: Complete separation from gp70, p30 and H‐2

Abstract: The possibility that some or all of the viral proteins, gp70, p30, and the histocompatibility antigen, H-2, function as the tumor-specific transplantation antigen (TSTA) of the R-MuLV-induced leukemia, RBL-5, and also in the secondary in vitro induction of cytotoxic T lymphocytes (CTL), was investigated. The antigen was obtained by isolating the plasma membranes of RBL-5 cells and solubilizing with sodium deoxycholate (DOC) followed by gel filtration chromatography. A fraction containing excellent tumor-reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1980
1980
1988
1988

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Hence, it is suggested that the FMR-MLV-immune T, may recognize an antigen other than gp70. This conclusion is consistent with the considerable evidence that has accumulated demonstrating that, in the systems studied so far, the MLVinduced tumor cell surface antigens responsible for eliciting the anti-tumor immune response in vivo are not carried on the MLV gp70 molecule (Alaba et al, 1979, and for review see Kurth et al, 1979). Further we (Zarling et al, 1978) and others (Gomard et al, 1978) have reported that a wide variety of high-titer xenogeneic antisera, raised against gp70 antigens purified from different MLV isolates, were unable to block the MLV-immune T, target-cell interaction.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, it is suggested that the FMR-MLV-immune T, may recognize an antigen other than gp70. This conclusion is consistent with the considerable evidence that has accumulated demonstrating that, in the systems studied so far, the MLVinduced tumor cell surface antigens responsible for eliciting the anti-tumor immune response in vivo are not carried on the MLV gp70 molecule (Alaba et al, 1979, and for review see Kurth et al, 1979). Further we (Zarling et al, 1978) and others (Gomard et al, 1978) have reported that a wide variety of high-titer xenogeneic antisera, raised against gp70 antigens purified from different MLV isolates, were unable to block the MLV-immune T, target-cell interaction.…”
Section: Discussionsupporting
confidence: 90%
“…These results can be interpreted to mean that immunity to the viral proteins on tumor cells may be sufficient to influence tumor growth as detected in virro. Our earlier report (Alaba et al, 1979) and the present data, however, show that RBL-5 cells have a unique TSTA separable from gp70 and p30.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the authors detected inhibition of cytolysis only of Gross-MLV-infected cells using a mixed population of Gross-MLV-specific CTL. Other reports (34,35) have suggested that the viral env gene products gp70 and p15 (E) could be target molecules recognized by CTL, but experiments designed to detect blocking of CTL activity by gp70 or anti-gp70 antibodies have yielded contradictory results (9,13,14). Flyer et al (10) demonstrated the existence of gp70-or p15 (E)specific CTL using a mixed population of CTL and target cells transfected with and expressing only the M-MLV env gene.…”
Section: A O T Bmentioning
confidence: 99%